Solid waste management at the university restaurant of the Federal Rural University of Pernambuco: diagnosis and analysis from the perspective of the environmental agenda for public administration - Gonçalves, Manuela Medeiros; Albuquerque, José de Lima (Revista de Administração da UFSM, 2020)
The amount of solid waste produced by the University Restaurant of the Federal Rural University of Pernambuco is quite high. Roughly 3.5k meals are served daily. A number which requires proper strategies for waste reduction. The research main goal was to run a diagnosis and an analysis on the management of the main waste generated at the University Restaurant: generation, collection and final destination on the perspective of the Public Administration’s Environmental Agenda. The data collection was conducted through documental research and direct observation with the intention of identifying the management stages of the main solid waste generated. The methodology used was a case study with a qualitative investigative approach. The results showed a lack of efficiency on the management of the main produced waste and that would require further attention to A3P’s variable that outlines the management of generated waste and the related legislation. Besides, it is noted that and adjustment of the food planning at the restaurant with the intention to reduce the disparity between the planned and the consumed amount of food. The results of this research, as well as the recommendations for future studies, will be forwarded to the managers of the restaurant so the necessary actions can be taken in order to ensure the continuous improvement of its waste management.